Two new species of Cybaeodes Simon, 1878 (Araneae, Liocranidae) and description of the male of C. magnus Ribera & De Mas, 2015 from the MSS in the eastern Prebaetic Mountain Range (eastern Spain) - Carles Ribera; Vicente M. Ortuño; Alberto Jiménez-Valverde; Marc Domènech (European Journal of Taxonomy)
Many species in the spider genus Cybaeodes Simon, 1878 have been described from caves and show marked adaptive characters to the underground environment, being considered troglobitic species. They have also recently been captured in the MSS (Mesovoid Shallow Substratum), a poorly known but species-rich habitat that lies between the superficial ground and the deep ground environment. Given the particular habitat of Cybaeodes and the difficulty of studying it, the diversity, biology and geographic distribution of this genus remain poorly known. The Prebaetic Mountain Range, in the Iberian Peninsula, appears to be a suitable region for this genus, from which three species are described from caves. In this work, we report on the taxonomic results of MSS samplings focused on the genus Cybaeodes in the region. Specimens were collected in alluvial and colluvial MSS using subterranean sampling devices. Samplings provided two new species for science, namely Cybaeodes bernia Ribera & Domènech sp. nov. and Cybaeodes gallinera Ribera & Domènech sp. nov. We also describe the male of Cybaeodes magnus Ribera & De Mas, 2015, previously unknown, and contribute new biogeographic data for Cybaeodes dosaguas Ribera & De Mas, 2015. This work increases our knowledge on the diversity and distribution of this still poorly known genus, and it highlights the importance of studying undersampled habitats such as the MSS.